ANALISIS PENERAPAN DEEP LEARNING DALAM PEMBELAJARAN DI SEKOLAH DASAR: STUDI EMPIRIS DI KOTA MATARAM - Muttaqin, Zainul; Hadi, Erwin; Hapipi, Hapipi; Jayadi, Usman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the application of deep learning technology in primary school education in Mataram City. Deep learning, as a branch of artificial intelligence (AI), has the potential to enhance learning effectiveness through personalized teaching materials and in-depth data analysis regarding students' development. The study focuses on four primary schools in Mataram City, namely SDN 45 Ampenan, SDN 18 Cakranegara, SDN 24 Cakranegara, and SDN 22 Mataram. The method used is a case study with a qualitative approach, involving interviews with teachers and school principals, as well as direct observations of the implementation of deep learning in the learning process. The results show that, although deep learning technology is still applied on a limited scale, its impact on improving the quality of learning, such as increased student motivation, better understanding of the material, and more accurate analysis of student development, is quite significant. However, the implementation of this technology also faces various challenges, particularly related to infrastructure limitations and the need for ongoing teacher training. This study recommends the need for improved infrastructure support and continuous training to maximize the potential of deep learning in primary education.